An edge/face-based smoothed radial point interpolation method for static analysis of structures. (July 2016) - Feng, S.Z.; Cui, X.Y.; Chen, F.; Liu, S.Z.; Meng, D.Y.
Abstract: This paper formulates an edge/face-based smoothed radial point interpolation method (ES/FS-RPIM) for the 2D and 3D static analysis of structures. In present method, the problem domain is discretized using triangular or tetrahedron cells and the edge-based or face-based smoothing domains are then constructed based on these background meshes. Field functions are approximated using RPIM shape functions which have Kronecker delta function property. An efficient T2L-scheme is employed for the RPIM shape function construction. The system equations are derived using the generalized smoothed Galerkin (GS-Galerkin) weak form and essential boundary conditions can be imposed directly as in the finite element method (FEM). Several numerical examples with different material models are investigated to verify the proposed method in terms of accuracy, stability, efficiency and convergence.